Community structure and microhabitat associations of cryptobenthic reef fishes in Veracruz, Mexico - Rivera-Higueras, Mariana; Hemingson, Christopher R.; Pouchoulen Alemán, Aurora de Monserrat; Cipolla, Kyra Jean M.; Souza, Philip M.; Brandl, Simon J. (Coral reefs, 2025)
Local habitat availability can strongly affect animal communities. On coral reefs, the biodiversity of small, bottom-dwelling (‘cryptobenthic’) reef fishes and drivers of their community assembly have yet to be explored in many locations. Here, we investigate how local and regional factors shape the structure and composition of cryptobenthic reef fish communities in the Veracruz Reef System National Park (VRS) in the Gulf of Mexico (GoM). Focusing on five reefs in the VRS, we surveyed cryptobenthic reef fish communities at scales of reef outcrops (~ 3–5 m 2 ) and isolated microhabitats, while also quantifying the benthic composition of each reef to determine microhabitat availability. We found no significant differences in species richness or abundance across park regions and reef zones, but community composition differed qualitatively across reef zones. Furthermore, we discovered strong differences in cryptobenthic reef fishes’ preferences for various microhabitats, which are likely to drive community assembly and provide evidence for species-specific vulnerabilities to reef degradation. Caves harbored the highest biodiversity and abundance of cryptobenthic fishes, while gorgonian soft corals and algae supported the fewest species and individuals. The endemic gobies Tigrigobius redimiculus and Elacatinus jarocho both showed high abundance and occurrence but displayed opposite patterns of microhabitat specialization; T. redimiculus was categorized as a microhabitat generalist, while E. jarocho was revealed as a cave-dwelling specialist species. Overall, our quantitative exploration of the cryptobenthic reef fish community in the southwest GoM provides a crucial baseline for habitat and biodiversity monitoring in the region and highlights E. jarocho as an emblematic, endemic indicator species that will be vulnerable to extinction if further reduction of habitat complexity occurs.